Dining out and the Risks of Food and Water Borne Illnesses (FWBI): A Case of Norovirus Outbreak on a Cruise Ship - Tulp, Orien L; Sainvil, Frantz; Karunyasopon, Vorachoat (Disease and Health Research: New Insights Vol. 8, 2024)
According to the CDC, approximately 48 million people become ill from foodborne and waterborne diseases each year, stemming from 10 or more commonly recurring noxious or pathophysiologic agents. The most common vector is the unintentional consumption of contaminated food, water, or beverages. A recent outbreak of norovirus occurred approximately 24 hours into a cruise, while passengers were en route to a Northern destination aboard a holiday cruise ship on a scheduled week-long journey. The symptoms of classic norovirus including watery diarrhea, severe abdominal cramps, and nausea were quickly recognized, and the illness causation was confirmed via on-board laboratory testing in the ship infirmary. Appropriate treatment was prescribed by the ship’s physician, and containment was realized within a few days. Because of the limited number of passengers affected (12 out of over 1,000), and the timing of the incident, it was concluded that the origin of the infection likely occurred prior to or soon after the passengers boarded, possibly linked to a welcoming ceremony hosted by the ship’s captain during which a variety of h’odoerve style finger foods including some seafood items were made available during a buffet dinner. Following the initial outbreak, no additional cases were reported or identified, no on-board origin was confirmed, and all passengers recovered without incident and continued the cruise. The study concluded that the clinical case and the accompanying overview of agents linked to food and water-borne illnesses underscore the challenges of managing infectious outbreaks on not only cruise ships but also exercising diligence during casual dining out at your favorite restaurant.